Revival? Rebirth? Renaissance? : What happened to Polish Jews over the last four decades? - Gebert, Konstanty (Nordisk judaistik/Scandinavian Jewish Studies, 2020)
Drawing on personal experience, the author discusses the vicissitudes of Jewish identity formation in the last two decades of Communist Poland and the first two decades which followed. He addresses the role of religion in the Jewish revival which occurred in that period, and sets it against other models of Jewish identity – Zionist, Yiddishist and assimilationist - on one hand, and the twin pressures of anti- and philosemitism in Polish society at large. This discussion is placed within the broader framework of the Polish political transformation. He finally suggests that the survival and revival of the Jewish community in Poland offers a more general lesson for the continuation of Jewish peoplehood.